2014
DOI: 10.1603/ec13455
|View full text |Cite
|
Sign up to set email alerts
|

Priming <I>Galleria mellonella</I> (Lepidoptera: Pyralidae) Larvae With Heat-Killed Bacterial Cells Induced an Enhanced Immune Protection Against <I>Photorhabdus luminescens</I> TT01 and the Role of Innate Immunity in the Process

Abstract: The current study investigated the characteristics and mechanism of the invertebrate immune priming using Galleria mellonella (L.) (Lepidoptera: Pyralidae) larvae (host) and Photorhabdus luminescens TT01 (pathogen) as a model. The following parameters of the G. mellonella larvae primed by hemocoel injection of heat-killed cells of TT01 or Bacillus thuringiensis HD-1 were determined at designated times after priming and then compared and analyzed systematically: mortality of the primed larvae against TT01 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 43 publications
3
35
0
1
Order By: Relevance
“…These findings indicate that the protective effect against an otherwise lethal septic infection with the same pathogen is probably due to “immunological loitering” rather than an enhanced ability to generate a second immune response. These results were further confirmed by another study that examined priming effects on the greater wax moth Galleria mellonella (19). Preinfection experiments revealed that challenging G. mellonella larvae with heat-killed P. luminescens or Bacillus thuringiensis bacteria confers a protective effect by prolonging the survival of insects subsequently infected with either of these pathogens.…”
Section: Immune Primingsupporting
confidence: 62%
“…These findings indicate that the protective effect against an otherwise lethal septic infection with the same pathogen is probably due to “immunological loitering” rather than an enhanced ability to generate a second immune response. These results were further confirmed by another study that examined priming effects on the greater wax moth Galleria mellonella (19). Preinfection experiments revealed that challenging G. mellonella larvae with heat-killed P. luminescens or Bacillus thuringiensis bacteria confers a protective effect by prolonging the survival of insects subsequently infected with either of these pathogens.…”
Section: Immune Primingsupporting
confidence: 62%
“…This possibility was supported by our previous study that used Galleria mellonella as the host and found dramatic increases in the counts of granular cells and plasmatocytes (phagocytes) after the larvae were primed with heat-killed bacteria (Wu et al, 2014). The phagocytic index was also a measure of the phagocytic ability of the phagocytes, which was estimated by the average fluorescence intensity of each phagocytic hemocyte and was dependent on the phagocytic receptor (Pearson et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…The in vitro phagocytosis quenching assay was performed according to the method described in our previous study (Wu et al, 2014).…”
Section: Phagocytosis Assay and Classification Of The Hemocytesmentioning
confidence: 99%
“…Phagocytosis refers to the engulfment of targets, such as bacteria or yeast, by an individual hemocyte and encapsulation results in the binding of hemocytes with larger targets, such as parasitoids and nematodes. In a previous study, we demonstrated that both granular cells and plasmatocytes in the hemolymph of Galleria mellonella phagocytosed FITC-labeled bacteria in vitro (Wu et al, 2014). During an encapsulation response, granular cells contacted the invaders first and then released material that promoted the attachment of plasmatocytes, eventually forming a smooth capsule comprised of overlapping layers of cells (Schmit and Ratcliffe, 1977;Pech and Strand, 1996).…”
Section: Introductionmentioning
confidence: 88%
“…The fluorescent bacteria were prepared as previously described (Wu et al, 2014). Briefly, TT01 was cultured in Luria-Bertani (LB) broth at 28°C with shaking at 200 rpm to an OD600 of approximately 1.5.…”
Section: In Vitro Phagocytosis Assay Using Fitc-labeled Bacteriamentioning
confidence: 99%